The Influence of Teacher Competence on Fiqh Learning Outcomes in Class VIII at MTs.S Nurul Iman - Sari, Desi Novita; Abdullah, Yusuf; Ismail, Yunus (Yayasan Pendidikan Islam Akmalia, 2023)
Nowadays there are still teachers who have not graduated from the Faculty of Teacher Training and Education, even though educational background is important for a teacher. These weaknesses lead to the low quality of education. An academic educational background that does not meet the requirements can have a negative influence on the teacher's teaching style, attitudes and behavior in teaching, and educational abilities. A teacher must have competence in teaching so that the expected goals can be achieved optimally so that student learning outcomes are affected. This research uses a quantitative approach with data collection techniques using interviews, documentary observation and closed questionnaires using Likert scale measuring instruments. The research results reveal that there is a high influence of teacher professional competence on the learning outcomes of class VIII students at MTs. S. Nurul Iman Padang Reba